2004
DOI: 10.1103/physreve.69.016113
|View full text |Cite
|
Sign up to set email alerts
|

Topology of large-scale engineering problem-solving networks

Abstract: The last few years have led to a series of discoveries that uncovered statistical properties, which are common to a variety of diverse real-world social, information, biological and technological networks. The goal of the present paper is to investigate, for the first time, the statistical properties of networks of people engaged in distributed problem solving and discuss their significance. We show that problem-solving networks have properties (sparseness, small world, scaling regimes) that are like those dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 31 publications
8
120
2
Order By: Relevance
“…Counter to the perspective that nodes have particular rolesKey Words: social networks, time-based networks, dynamic hubs, multiscale networks, turbulent networks R ecent advances have demonstrated that the study of universal properties in physical systems may be extended to complex networks in biological and social systems [1][2][3][4][5]. This has opened the study of such networks to experimental and theoretical characterization of properties and mechanisms of formation.…”
mentioning
confidence: 99%
“…Counter to the perspective that nodes have particular rolesKey Words: social networks, time-based networks, dynamic hubs, multiscale networks, turbulent networks R ecent advances have demonstrated that the study of universal properties in physical systems may be extended to complex networks in biological and social systems [1][2][3][4][5]. This has opened the study of such networks to experimental and theoretical characterization of properties and mechanisms of formation.…”
mentioning
confidence: 99%
“…Some network centrality measures have been applied, for the first time, to large-scale engineering design and product development networks by Braha and Bar-Yam in (Braha and Bar-Yam 2004b, Braha and Bar-Yam 2004a, Braha et al 2006, Braha and Bar-Yam 2007. These works have provided two interesting results.…”
Section: Introductionmentioning
confidence: 71%
“…Recent studies [1][2][3] provide the first empirical and theoretical explanation for the patterning of information flows in large-scale project environments. Information flow data of four large-scale projects was reconstructed by detailed field study in several major companies in the US and UK [1][2][3].…”
Section: Structural Properties Of Complex Product Development Networkmentioning
confidence: 99%
“…, and a set of lines } ,..., , { 2 1 L e e e E = between pairs of nodes. If the line between two nodes is non-directional, then the network is called undirected; otherwise, the network is called directed.…”
Section: Structural Properties Of Complex Networkmentioning
confidence: 99%
See 1 more Smart Citation